Two-year motor outcomes associated with the dose of NICU based physical therapy: The Noppi RCT. (November 2022) - Øberg, Gunn Kristin; Handegård, Bjørn Helge; Campbell, Suzann K.; Ustad, Tordis; Fjørtoft, Toril; Kaaresen, Per Ivar; Girolami, Gay L.
Abstract: Background: Interventions involving both the parent and the preterm infant have demonstrated lasting effects on cognitive outcomes, but motor effects are less salient. It remains unclear when to commence early intervention and if dosages have impact on motor outcomes. Aims: To examine the effect on motor performance at 24-months corrected age following a parent-administered intervention performed with infants born preterm in the NICU. Intervention dosing and longitudinal motor performance were also analyzed. Study design: Single-blinded randomized multicenter clinical trial. Subjects: 153 infants born, gestational age ≤ 32 weeks at birth, were randomized into intervention or control group. Outcome measures: Infant Motor Performance Screening Test, Test of Infant Motor Performance, Peabody Developmental Motor Scales-2. Results: No significant difference was found between the intervention and the control group assessed with the PDMS-2 at 24-months CA. However, a significant positive association was found between dosing and the Gross Motor and Total Motor PDMS-2 scores. Analysis of longitudinal motor performance showed a decreasing motor performance between 6- and 24-months corrected age in both groups. Conclusions: There was no difference in motor performance between groups at 24-months corrected age. However, increased intervention dosage was positively associated with improved motor outcome. Highlights: Dosage of NICU intervention for preterm infants linked to motor outcome at 24 months. NICU interventions provided by parents associated with positive long term outcomes. Ongoing guidance is important for parents delivering interventions in the NICU.